2012
DOI: 10.3354/meps09428
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and ecological implication of eelgrass life history strategies near the species’ southern limit in the western North Atlantic

Abstract: Eelgrass Zostera marina L. populations located near the species southern limit in the western North Atlantic were assessed monthly from July 2007 through November 2008. We identified (1) dominant life history strategies and local environmental conditions in southern Z. marina populations, (2) quantified differences in reproductive phenology between populations and different local environmental conditions, and (3) compared reproductive strategies to established annual and perennial life history paradigms. Obser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 56 publications
3
45
0
Order By: Relevance
“…This experiment demonstrated that CO 2 stimulation of primary production can enhance the summertime survival, growth, and proliferation of perennial eelgrass from the Chesapeake region that is regularly impacted by summer heat stress (Moore & Jarvis 2008, Jarvis et al 2012. These results reinforce the emer ging paradigm that eelgrass may benefit significantly from a high-CO 2 world.…”
Section: Discussionsupporting
confidence: 75%
“…This experiment demonstrated that CO 2 stimulation of primary production can enhance the summertime survival, growth, and proliferation of perennial eelgrass from the Chesapeake region that is regularly impacted by summer heat stress (Moore & Jarvis 2008, Jarvis et al 2012. These results reinforce the emer ging paradigm that eelgrass may benefit significantly from a high-CO 2 world.…”
Section: Discussionsupporting
confidence: 75%
“…This submerged plant creates shelter for ecologically and economically important faunal species, enhances biodiversity, contributes to sediment stability, carbon and nutrient storage, and improves water clarity (Gutiérrez et al 2011, Duarte et al 2013. Eelgrass is the most widely dis-tributed seagrass species across a range of latitudes, from warm temperate waters up to northern Arctic regions (den Hartog 1970, Jarvis et al 2012, Olesen et al 2015. Distinct life history strategies and a wide tolerance to a range of salinity and temperature conditions allow this seagrass species to exploit areas from brackish estuaries to open oceans over a large geographical range (den Hartog 1970, Walker et al 2001, Lee et al 2007a, Nejrup & Pedersen 2008.…”
Section: Introductionmentioning
confidence: 99%
“…High water temperatures decrease growth and increase mortality, and these negative effects may be exacerbated by the interaction with other stressors such as reduced light availability, low salinity, or low oxygen levels (Olesen & Sand-Jensen 1993, Nejrup & Pedersen 2008, Raun & Borum 2013. Hence, diebacks have been recorded at summer temperatures above 25°C (Orth & Moore 1986, Sfriso & Ghetti 1998, Moore & Jarvis 2008, and at the southern distribution limit eelgrass populations may adopt an annual or a mixed-annual life strategy to escape the warm summertime conditions (Phillips & Backman 1983, Meling-López & Ibarra-Obando 1999, Jarvis et al 2012. Water temperature also affects the timing of life-history events with progressively later flowering and seed maturation at increasing latitudes , Silberhorn et al 1983.…”
Section: Introductionmentioning
confidence: 99%